Aplikasi BAP (Benzyl Amino Purin) untuk Sambung Dini pada Pembibitan Durian (Durio zibethinus L) - Miranda Novia Fitri; Armaini Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Mini grafting durian was a vegetative propagation to produce superior durian seedlings. The success of mini grafting is determined by the availability of hormones in the seed. Plants that lacking of phytohormone can inhibit the growth of seedlings. Therefore, an attempt was made to fulfill phytohormone by providing BPT. The purpose of this research was to determine the effect of BAP and get the best concentration in increase the success and growth of mini grafting durian. This research was conducted experimentally and used a complete random sampling. The sample was taken by randoml as much as two samples each unit experiment. The tasted treatment was the ZPT treatment wich consist BAP, 50 ppm BAP, 100 ppm and 150 ppm. The parameters observed were the percentage of the seedlings growing, shoot growth time, number of shoots, number of leaves, increasing of system diameter, increasing seedling height, fresh weight and dry weight of seedlings. The use of BAP has no effect on the growth of seedlings durian result of mini grafting, but the highest percentage of success rate mini grafting was obtained giving BAP 50 ppm. The growth of mini grafted durian seedlings including the complete amount, the number of leaves, the increase in diameter of the stem, the fresh weight and dry weight of the seeds obtained tendency of the best results in the treatment of 150 ppm. Keywords: Durian, mini graftting, cytokinin, BAP